2021
DOI: 10.1002/ppsc.202000271
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots and Stability of Their Optical Properties

Abstract: exploited for fabrication of light-emitting devices, [5] and their remarkable electronic properties have been used in the fields of photovoltaics [6] and electronics. [5d,7] Low toxicity and the excellent biocompatibility of CDs encourage researchers to study the role of CDs in the biomedical field, and many bioimaging [8] and drug delivery [9] applications of CDs have been reported. The dependence of the optical properties of CDs on the presence of metal ions in dispersion has been exploited for cation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 150 publications
(141 reference statements)
1
51
0
Order By: Relevance
“…In such CD samples, high blue emission may come from molecular fluorophores, [ 40 ] which is prone to photobleaching. [ 44 ] These features not only suggest the high fluorescence stability of Y‐CDs, but also imply the distinctive chemical structure and underlying emission mechanism of Y‐CDs differed from those of well‐known CDs with high blue emission. Therefore, the resultant Y‐CDs have a large Stokes shift, an ultra‐high PL QY, and good fluorescence stability, which is beneficial for further applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such CD samples, high blue emission may come from molecular fluorophores, [ 40 ] which is prone to photobleaching. [ 44 ] These features not only suggest the high fluorescence stability of Y‐CDs, but also imply the distinctive chemical structure and underlying emission mechanism of Y‐CDs differed from those of well‐known CDs with high blue emission. Therefore, the resultant Y‐CDs have a large Stokes shift, an ultra‐high PL QY, and good fluorescence stability, which is beneficial for further applications.…”
Section: Resultsmentioning
confidence: 99%
“…B‐CDs possessing similar size distribution but with lattice mismatch (Figure S5, Supporting Information) and showing more non‐polar groups (fatty linkages) on the surface (Figures S1 and S6, Supporting Information) and faster biexponential decay (Figure S4, Supporting Information) might have different underlying emission mechanism. [ 1,4,33,44 ]…”
Section: Resultsmentioning
confidence: 99%
“…Carbon dots (CDs) have received increasing attention owing to their excellent biocompatibility, good water solubility, low cytotoxicity, robust chemical inertness, high photo/chemical stability, and strong resistance to photobleaching [ 1 , 2 ]. They have especially demonstrated huge potential applications in a wide range of fields, such as sensing, bioimaging, drug delivery, photocatalysis, energy storage, anticounterfeiting, light-emitting diodes (LED), and so on [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CDs are known to have better photostability than molecular optical probes, but they become unstable under long-term exposure to light. [21][22][23] Continuous UV excitation leads to changes in the chemical structures within CDs, resulting in a decrease in the QY. 24 In addition, it has been reported that the photodegradation of CDs can cause cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%